Do monólogo ao diálogo : uma crítica às práticas educativas - Oliveira, Fernanda Felix de (2019)
The aim of this research is to problematize particular characteristics of the dialogue as a form of communication morally superior to the monologue, examining the values present in the monologue that must be considered in the education field. The primary intent is to analyze how the dialogue has exerted an hegemonic domination that believes in its superiority in relation to the subjects’ emancipation in educational praxis insofar. Then, the main attributions present in the dialogue regarding its normative concept are explored, as well as the characteristics required to participate in this intersubjective relationship. For that, a historical-philosophical analysis is made on the origin of dialogue. As the main reference to the construction of dialogue, Socrates is used as the first educator of the dialogue, in order to understand its influences in the conception of dialogue and dialectics. The Critical Pedagogy and the conception of Paulo Freire, as well as his influences on dialogue in education are scrutinized. Through a critical and investigative study, the aim is to question the dialogue hegemony in modern discourses on education. For this, the studies of the philosophers Martin Buber and Emmanuel Levinas are used aiming at understanding and analyzing the intersubjective and ethical relations, constituents of the relation of the Self with the Other. Tone Kvernbekk’s work supports a counterpoint to the hegemonic view of dialogue where she postulates that there are values in the monologue that need to be observed. It is concluded, therefore, that the monologue should be a practice that promotes dialogue. That is, monologue can be seen in education as a necessary condition but not sufficient for teaching-learning. Therefore, the monologue can be considered the first stage to develop skills necessary towards the effective participation of the subjects in the dialogue.